2002
DOI: 10.1177/000348940211100203
|View full text |Cite
|
Sign up to set email alerts
|

Unloaded Shortening Velocity and Myosin Heavy Chain Variations in Human Laryngeal Muscle Fibers

Abstract: Myosin description in human laryngeal muscles is incomplete, but evidence suggests the presence of type I, IIA, IIX, and tonic myosin heavy chain (MHC) fibers. This study describes the unloaded shortening velocity (V0) of chemically skinned laryngeal muscle fibers measured by the slack test method in relation to MHC content. Skeletal fibers from human laryngeal and limb muscle biopsy specimens were obtained for determination of V0, and subsequently, glycerol-sodium dodecyl sulfate-polyacrylamide gel electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
1
46
0
3
Order By: Relevance
“…The fact that extraocular myosin does not have light chains should not have an effect on ATPase activity based on experiments on skeletal muscle myosin (60). Several studies have shown that fibers expressing MyHC-Extraocular exhibit isometric contraction twitch times twice as fast as those from conventional skeletal muscles (29,67). The unique requirements of extraocular muscles, which contract very rapidly, repetitively, and for prolonged periods against very low load to move the eye and laryngeal muscles may indicate a specialized role for this isoform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that extraocular myosin does not have light chains should not have an effect on ATPase activity based on experiments on skeletal muscle myosin (60). Several studies have shown that fibers expressing MyHC-Extraocular exhibit isometric contraction twitch times twice as fast as those from conventional skeletal muscles (29,67). The unique requirements of extraocular muscles, which contract very rapidly, repetitively, and for prolonged periods against very low load to move the eye and laryngeal muscles may indicate a specialized role for this isoform.…”
Section: Discussionmentioning
confidence: 99%
“…The ATPase activities of the developmental and the MyHC-Extraocular isoforms are less clear due to their heterogeneous expression with other isoforms. Preliminary work suggests the developmental myosins have low ATPase activities (31,32), while MyHCExtraocular is thought to be a very fast myosin (22,29,33). All of this evidence points to the conclusion that myosin isoform expression patterns are a likely mechanism for the specialization of muscles to perform specific tasks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Laryngeal muscles in mammals are fast, but do not reach such high contraction rates as starling muscles (Martensson and Skoglund, 1964;Alipour-Haghighi et al, 1987;Alipour and Titze, 1999;Sciote et al, 2002;Hoh, 2005). Unlike toadfish sonic and rattlesnake tailshaker muscles, laryngeal muscles show heterogeneous fibre type composition (Hoh, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that some of these unusual MyHC isoforms are present in the PCA given the evidence of these isoforms in other specialized cranial muscles, and the unusual shortening velocities reported for these fibers. 4,5 Anatomical studies have shown a reliable presence of horizontal and vertical components of the posterior cricoarytenoid (PCA) muscle, but minimal information exists regarding the composition and function of these muscle subcompartments. 6 Innervation studies have demonstrated a distinct innervation pattern to different intrinsic laryngeal muscle subcompartments.…”
Section: Introductionmentioning
confidence: 99%